Kitchen Gardens: From the White House to Your House - English, Jean; Fox, Douglas (Maine Policy Review, 2011)
This short article discusses how having small “kitchen gardens” can reduce fossil inputs, keep food and energy dollars in local communities, and add resilience for individuals and local economies in the face of economic downturns.